2018
DOI: 10.18287/jbpe18.04.040301
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hyperspectral analysis of skin hemoglobin and melanin content for neoplasia detection

Abstract: We present results of main skin chromophores (melanin and hemoglobin) optical analysis. Analysis of 91 in vivo skin tissues (50 benign and 41 malignant) was performed in visible spectral region with hyperspectral imaging technique. To assess the malignancy of skin tissues we proposed two methods for calculating the integral index of tissue optical density and performed a comparison of their effectiveness and effectiveness of physician survey. As the main diagnostic feature, we propose to use data of integral o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Previously, studies of hyperspectral imaging were conducted in Refs. [19,20] to determine the types of human skin neoplasms. These studies have shown a fairly high accuracy in determining pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, studies of hyperspectral imaging were conducted in Refs. [19,20] to determine the types of human skin neoplasms. These studies have shown a fairly high accuracy in determining pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, dermoscopy was the fastest device to obtain skin images. Recently, the use of HSI for the diagnosis of skin cancer has shown excellent performances ( 87 , 88 ). Figure 3 shows general steps of HSI body surface inspection.…”
Section: Hsi Applications In Tumor Detectionmentioning
confidence: 99%